The Influence of Learning Facilities and Infrastructure on Students' Learning Motivation - Nurul Rahma; Askar Askar; Masmur M (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) IAI Al Urwatul Wutsqo - Jombang, 2026)
The purpose of this study was to determine the effect of learning facilities and infrastructure on students' learning motivation. This study was conducted at SD Islam Terpadu Persis, Palu City. The approach used in this study was quantitative research with an associative design. In this study, the data collection methods used were questionnaires, observation, and documentation. The research sample consisted of 48 students selected through stratified random sampling techniques. The results of the hypothesis test showed that the significance value <0.05 H0 was rejected and Ha was accepted. Based on the hypothesis test, it can be concluded that there is an influence between learning facilities and infrastructure on students' learning motivation. Hypothesis proof was carried out using a T-test. This is shown in the t-table value, t count = 5.420 > t table = 2.012 so it can be said to be significant. Furthermore, the results of the determination coefficient test = 0.390 indicate that learning facilities and infrastructure contribute 39% to students' learning motivation, while the remaining 61% is influenced by other factors. The conclusion of this study states that there is a significant relationship between the influence of learning facilities and infrastructure on students' learning motivation at Persis Integrated Islamic Elementary School, Palu City